The Hymenoptera venom study III: Safety of venom immunotherapy - Lockey, Richard F.; Turkeltaub, Paul C.; Olive, Emory S.; Hubbard, James M.; Baird-Warren, Irene A.; Bukantz, Samuel C. (Journal of allergy and clinical immunology, 1990)
One thousand four hundred ten (44%) of the 3236 subjects in the Hymenoptera venom study accepted venom immunotherapy (VIT). Time to maintenance averaged 95 days, and the largest number achieved maintenance (147 subjects, 10.4%) at day 56. Ninety-two percent of the treated subjects achieved maintenance, and 84% continued therapy, most subjects (91%) until the study was terminated. One hundred seventy-one subjects (12%) experienced 327 treatment systemic reactions (Srs). The incidence of pruritus and angioedema/urticaria was similar with mild, moderate, or severe SRs. The SR severity did not correlate with the severity of the most recent sting before entry into the Hymenoptera-venom study, the most severe historical sting SR, the most severe SR during venom skin tests, the total dose of venom, the degree of skin test reactivity, or the lowest concentration yielding a positive skin test. Most SRs occurred between 1 and 50 μg and at maintenance; honeybee or wasp venoms were most likely to produce SR. This study, the largest of its kind with the use of standardized extracts, demonstrates (1) that there was good compliance, (2) that various historical and diagnostic criteria did not predict SRs to VIT, (3) that SRs to VIT were most likely to occur between 1 and 50 μg and at maintenance, (4) that honeybee or wasp venoms were most likely to produce an SR, and (5) that VIT is relatively safe.